Determination of Solar Radiation Distribution in Peninsular Malaysia - Lau, Pin Zhen (2013)
This is a study to evaluate the solar radiation distribution and availability as natural energy in Peninsular Malaysia. Malaysia is moving towards sustainable usage of energy and it has plenty of sunshine for the whole year which suitable using solar energy as the electricity generation. From the study, it can determine that which locations are suitable for building photovoltaic. Not all places in Peninsular Malaysia are suitable for solar panel construction due to some areas having more rainfall such as in Taiping which decreases the solar radiation reaches the earth due to cloud cover. The higher cloud covers percentage, the lower the solar radiation reaches the earth. In the study, sky photos are taken by camera on experiment site and NOAH image from satellite are taken from MMD to collect its digital numbers (DN) which will then convert into radiance. The radiance calculated from the formula is used to compare with the data references to show the solar radiation trend and to show which method is suitable in measuring solar radiation. The solar radiation is direct influenced the average land surface temperature (LST) which means increased in solar radiation will increase the land surface temperature. The result is then used to estimate solar radiation for other places where solar instrument is not available and finally a map that shows the solar radiation for Peninsular Malaysia is developed by using extrapolation method.